Vascular smooth muscle TRPC3 channels facilitate the inverse hemodynamic response during status epilepticus - Cozart, Michael A. (2020)
Human status epilepticus (SE) is associated with a pathological reduction in cerebral blood flow termed the inverse hemodynamic response (IHR). Canonical transient receptor potential 3 (TRPC3) channels are integral to the propagation of seizures in SE, and vascular smooth muscle cell (VSMC) TRPC3 channels participate in vasoconstriction. Therefore, we hypothesize that cerebrovascular TRPC3 channels may contribute to seizure-induced IHR. To examine this possibility, we developed a smooth muscle-specific TRPC3 knockout (TRPC3smcKO) mouse. To quantify changes in neurovascular coupling, we combined laser speckle contrast imaging with simultaneous electroencephalogram recordings. Control mice exhibited multiple IHRs, and a limited increase in cerebral blood flow during SE with a high degree of moment-to-moment variability in which blood flow was not correlated with neuronal activity. In contrast, TRPC3smcKO mice showed a greater increase in blood flow that was less variable and was positively correlated with neuronal activity. Genetic ablation of smooth muscle TRPC3 channels shortened the duration of SE by eliminating a secondary phase of intense seizures, which was evident in littermate controls. Our results are consistent with the idea that TRPC3 channels expressed by cerebral VSMCs contribute to the IHR during SE, which is a critical factor in the progression of SE.